Factors predicting satisfaction of Private Universities’ students in Selangor, Malaysia / Wong Chee Hoo, Alex Lee and Wong Yee Fong - Chee Hoo, Wong; Lee, Alex; Yee Fong, Wong (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Student satisfaction, a factor increasing in importance as it continues to influence the development and operation amongst private universities in Malaysia. This research focuses on this factor, amongst others, in their roles in affecting undergraduate students’ satisfaction in private universities in Selangor, Malaysia. With higher education being an intangible service rather than a tangible product, this research seeks to hypothesise and analyse the relationship between service quality in the context of tangibility, assurance, reliability, responsiveness, and empathy. In this study, the research objectives and questions were highlighted, and a conceptual framework that integrates different factors influencing the satisfaction of undergraduates is proposed. A 5-point Likert scale survey (N=288) was conducted; data were analysed using Multiple Regression Analysis through SPSS. Three factors, tangibility, assurance and empathy, showed a significant influence in predicting students’ satisfaction amongst private university students.